2011
DOI: 10.5897/ajb11.2444
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effects of Trichoderma harzianum and some mycorrhizal fungi on plant growth and against Rhizoctania solani Kühn in Lilium under in vivo conditions

Abstract: This study was conducted to determine the effects of microbial fertilizer containing Trichoderma harzianum Kuen 1585 (Tr), biological preparation (BRDI) (containing Glomus aggregatum, G. clarim, G. deserticola, G. intraradices, G. monosporus, G. mosseae, Gigaspora margarita and Paraglomus brasilianum), and Glomus sp. collected from agricultural areas in Aydin province on plant growth in Lilium and Rhizoctonia solani Kühn. (Rs) bulb and root rots under in vivo conditions. Study was conducted in 2 stages: at sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
1
0
1
Order By: Relevance
“…This may be due to Trichoderma spp. this access nutrients, increased solubility of insolubly compounds as well as increased availability of micronutrients by result of increased plant growth and flower diameter (Altmore et al 1999 and Yedidia et al 2001) [1,32] The results are in conformity with the finding of Anusuya et al (2003) [3] in carnations, Sirin (2011) in lilium, Dubey et al (2008) [8] in gladiolus and (Shrma and Chandel, 2013) in carnation.…”
Section: Flowering Parameters Flower Diameter (Cm)supporting
confidence: 61%
“…This may be due to Trichoderma spp. this access nutrients, increased solubility of insolubly compounds as well as increased availability of micronutrients by result of increased plant growth and flower diameter (Altmore et al 1999 and Yedidia et al 2001) [1,32] The results are in conformity with the finding of Anusuya et al (2003) [3] in carnations, Sirin (2011) in lilium, Dubey et al (2008) [8] in gladiolus and (Shrma and Chandel, 2013) in carnation.…”
Section: Flowering Parameters Flower Diameter (Cm)supporting
confidence: 61%
“…Treating sunflower plants with Glomus sp. and T. harzianum fungi led to increase in the effectiveness of enzymes in defending against pathogens and found that inoculating plants with these bio-agents led to an increase in effectiveness of peroxidase which in turn increases resistance against R. solani (38).…”
Section: Isr By G Mosseae and T Harizanum On Cucumber Plants Infected By A Alternata In Plastic Potsmentioning
confidence: 99%
“…Topraklı yetiştiricilikte Rhizoctonia solani, Phytophthora ssp., Fusarium spp., Verticillium spp., Pythium spp., Botrytis sp. gibi toprak kaynaklı hastalık etmenleri başarısızlıklara neden olmaktadır (Miller, 1998;Chase, 2005;Gümrükçü ve Gölükçü 2005;Şirin, 2011). Ancak seralarda yapılan yetiştiricilikte toprakların fiziksel ve kimyasal yapılarının uygun olmaması, monokültür uygulamalar, bilinçsiz gübrelemeler, kimyasal madde kullanımı ve tuzluluğun artması gibi nedenlerle toprak yorgunlukları yaşanması kesme çiçek verim ve kalitesini etkilediği gibi aynı zamanda üretim materyali olan yavru soğan oluşum miktarını ve kalitesini etkilemektedir.…”
Section: Introductionunclassified